The Effect of Remittances on Child’s Work Participation Age 10-17 in Indonesia - Sihotang, Berliana Deborah; Susanti, Hera (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The phenomenon of child labor has been a problem in Indonesia. One of the factors most often cited as the cause of child labor is poverty.  The ILO revealed that one of the ways to get out of poverty is by doing a migration. Migration through remittances sent by migrants become an alternative income for households so that children don't have to enter the world of work just to meet their daily needs. Using the 2SLS method and with the help of an instrumental variable, this study found that remittance had a negative and significant effect on children's work participation.